Analisis Kinerja Keuangan dan Faktor-faktor yang Mempengaruhi (Studi Kasus pada Pemerintah Daerah Kabupaten Subang) - Nabila Ayudya Maharani; Arwan Gunawan; Dian Imanina Burhany (Indonesian Accounting Research Journal, 2021)
This study aims to analyze financial performance using financial independence ratios, PAD effectiveness ratios, PAD efficiency ratios and regional spending efficiency ratios and to find out the factors that influence it on the Subang Regency local government in the 2014-2018 fiscal year. The research method used is quantitative methods and qualitative methods. Sources of data taken in this study are secondary data and primary data using a credibility test with triangulation and member check techniques. The results showed that the financial performance of Subang Regency was seen from the average independence ratio of 17.66% (very low), the effectiveness ratio of PAD was 110.97% (very effective), the efficiency ratio of PAD was 3.16% (very efficient), and the average efficiency ratio of spending is 92.17% (efficient). The factors that affect the financial independence of Subang Regency are due to the Regional Original Income and Balancing Funds, and the factors that affect the effectiveness and efficiency of PAD and the efficiency of spending are caused by four factors, namely planning, implementation, regulation, and human resources factors. Efforts were made to improve financial performance by increasing PAD through intensification and extensification strategies and improving the quality of human resources by holding technical guidance and training.